Mechanism of wear of eutectic coverages Fe-Mn-C-B-Si-Ni-Cr - Пашечко, М.І.; Дзєдзіц, К.; Барщ, M. (Problems of Tribology, 2014)
Wear mechanism of eutectic coatings based on Fe-Mn-C-B-Si-Ni-Cr system was studied. The coatings were obtained by gas metal arc welding (GMA) with use of wire powder. Pin-on-disk dry sliding wear tests at sliding speeds 0,4 m/s and under loads ranging from 3 to 10 MPa were conducted for pin specimens with eutectic coatings. Material of counter-sample was steel C 45. During frictions a typical tribological behavior was observed. After friction atomic segregations in the eutectic coatings due to wear was studied by scanning electron microscopy (SEM) and mass spectroscopy. Structure and distribution of atoms of the friction surface were determined by energy dispersive spectroscopy (EDS). An increased content of C, B, Si at a friction surface was revealed.